Peningkatan Hasil Belajar Siswa MAN Bandung Barat pada Materi Fungi melalui Direct Instruction PowerPoint - Rauuf, Euis Rizkika; Chusni, Muhammad Minan; Kariadinata, Rahayu (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study aims to improve the learning outcomes of students at MAN Bandung Barat on the topic of Fungi through the implementation of the Direct Instruction learning model supported by PowerPoint media. The background of this research stems from the low level of students’ conceptual understanding of the material, indicating the need for a more structured and guided instructional approach. The research employed a quantitative method with a one-group pretest–posttest design. The subjects of the study were Grade X students enrolled in biology classes during the current semester. The research procedure included administering a pretest, conducting the learning intervention using the Direct Instruction model facilitated by PowerPoint, and administering a posttest to measure changes in learning outcomes. Data analysis consisted of descriptive statistics, a normality test using the Kolmogorov–Smirnov method, and the calculation of the N-Gain score to determine the effectiveness of the intervention. The results showed a significant increase in the average scores from the pretest to the posttest, indicating a positive improvement after the treatment was administered. The normality test results confirmed that the data were normally distributed (p > 0.05), allowing for appropriate subsequent analyses. The average N-Gain score fell into the moderately effective category, suggesting that the learning intervention meaningfully enhanced students’ understanding. Therefore, this study concludes that the application of the Direct Instruction model supported by PowerPoint is effective in improving students’ learning outcomes on the topic of Fungi. The findings further imply that structured instructional models combined with visual media can optimize students’ comprehension of biological concepts.